(untitled) (Politeja, 2020)
The Term ‘Spouse’ in EU Law – Comments on the Judgment in the Coman Case (C‑ 673‑16) The paper concerns the judgment of 5 June 2018 issued by the Court of Justice of the European Union in the Coman case (C‑673‑16), in which the Court for the first time defined the term ‘spouse’ for the purpose of Directive 2004/38 on the right of citizens of the Union and their family members to move and reside freely within the territory of the Member States. It discusses the consequences of the judgement and its relation to the traditional mechanisms of private international law and the EU principle of mutual recognition.